The work-family balance experiences of production couples operating Chinese Cut, Make and Trim factories in Newcastle, South Africa - Ma, Yuh-Wen (Organisational Psychology, 2022)
The purpose of this study was to develop a deep understanding into the unique work family balance experiences of women in production couples in cut, make and trim factories in Newcastle, South Africa. A production couple is first and foremost a business partnership that involves joint ownership of a clothing factory, however the relationship is also a strategy the women use to satisfy their emotional needs and over time the relationship plays an important role in their return migration intention. Using a phenomenological research design, eight in depth semi-structured interviews were conducted with women in a production couple. Though the study set out to explore both the male and female partners, all the male partners eventually declined, citing Covid-19 related reasons such as having the only male in the researcher network dropping out, significantly lowering the likelihood of recruiting willing male participants. A potential reason for this is that men in Chinese culture are expected to carry the family name and with the persisting patriarchal gender roles (Sun & Chen, 2014), they are confronted with greater risk of losing face if exposed that they are in this type of relationship. Thematic analysis conducted on the data revealed three key themes: (1) Factors affecting the work-family balance of women in production couples, (2) Transnational care practices and, (3) Boundary management practices used by the women to maintain work-family balance. The findings challenged the nuclear family ideal and contributed new knowledge on how work family balance is perceived and maintained from a transnational perspective.